Antenatal risk factors in emergency caesarean sections done for fetal distress - Aiyer Kohli, Uttara; Singh, Sanjay; Dey, Madhusudan; Kaur Bal, Harpreet; Seth, Atul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Fetal distress is an important indication for emergency caesarean deliveries. The objective of this study is to identify the antenatal and intrapartum risk factors in emergency caesareans done for non-reassuring fetal status and compare with patients who underwent emergency caesareans for other indications. Methods: It was a retrospective study and data was collected from the labour room records of a tertiary care hospital. Patients undergoing emergency caesareans for fetal distress were the cases and the remaining emergency caesareans were the controls. Data was statistically analyzed. Results: There were 5184 deliveries during this period of which, 669 were emergency caesareans. 126 (18.83%) of these were due to fetal distress/ non-reassuring fetal status and 543 (81.17%) were for other indications. Caesarean due to fetal distress accounted for 2.43% of the total deliveries. There were more primigravidae (61.11% Vs 46.04%) in the fetal distress group (Odds Ratio 1.84, p=0.003). Intra uterine growth restriction (OR 5.44, p<0.0001) and antepartum haemorrhage mainly due to abruption (OR 11.19, p <0.0001) were other important antenatal risk factors. Those with neonates of birth weight between 1.5 to 2.0 kgs were more likely to undergo emergency caesarean for fetal distress (OR 1.78, p=0.0435). The risk of a lower APGAR was higher in the fetal distress group (12.59%). 28.34% neonates in this group required NICU admission. Conclusions: Primiparity, intrauterine growth restriction, antepartum hemorrhage and prematurity, have shown to significantly increase the risk of emergency cesareans due to non-reassuring fetal status. We need to improve antenatal care with a goal of early detection of the above risk factors for timely institution of appropriate intervention and thus contributing to a reduction of emergency caesareans due to fetal distress.